Aux frontières de l’identité : pronoms, classificateurs et focalisation narrative dans Membrane de Chi Ta-wei - Coraline Jortay (MONDE CHINOIS NOUVELLE ASIE, 2022)
As science-fiction as a genre remains largely dominated by English-language works, what narrative and stylistic contributions can languages such as Chinese bring? How do they impact themes and literary representations considered against the genre as a whole? Taking as a starting point the classifier and pronominal systems of Chinese and their use in the Taiwanese novella The Membranes (Mo 膜) by writer, translator and ku’er (酷兒) theorist Chi Ta-wei (紀大偉), this paper aims to show how those linguistic categories take part in thematising queer in the novella. Indeed, while The Membranes’ androids and narrative universe emerge at the crossroads of a globalized imagination and the evolution of socio-political realities in Taiwan from the late eighties onwards, its take on hybridity and the fluidity of sexual and biological identities seems to be grappling with surface contradictions that can only be unravelled through a deeper analysis of the linguistic mechanisms at stake in the novella. Contextualised against a double chronology of ku’er and science-ficton literature in Taiwan, as well as an overview of similar linguistic strategies in Anglophone science-fiction, The Membrane then allows us to widen our perspectives on the contribution of non-anglophone literary production to the wider science-fiction genre